English as a Medium of Instruction in Nigerian Secondary Schools: Its Effects on Academic Performance and Students’ Perceptions - Lumi, Esther; Aliyu, Muhammad Mukhtar ((JELE) Journal Of English Language and Education, 2021)
The government, teachers and parents have expressed their concerns over the poor academic performance of many secondary school students. Therefore, the study aims to investigate the extent to which English influences the academic performance of secondary school students. The study employed a case study research design and qualitative and quantitative data were collected. Semi-structured interviews were conducted for the qualitative data while students report sheets of the second term 2020/2021 academic session was used as a source of the quantitative data. The study selected a complete class of fifty-two (52) students in north-eastern Nigeria. The finding revealed the average scores of the students’ performance of students in all the subjects taught using English as a medium of instruction were less than 45% average scores while in the subjects taught using Hausa medium the average score is 50% and above. Furthermore, the results showed that students have negative attitudes toward the use of English as a medium of instruction. They perceive English as a difficult language while viewing Hausa as a better medium for learning in secondary schools. Lastly, the findings further revealed that there is a psychological impact on the students as regards the use of English as a medium of instruction. Using English makes them feel uncomfortable and embarrassed when they do not understand some words or when they are asked to speak or ask questions. The study makes some recommendations to improve the academic performance of students and further research.